Attitudes toward Online Dating among Students Studying in Austria - Jeknić, Jelena; Milfelner, Borut (Naše gospodarstvo/Our economy, 2014)
The aim of this paper is to study attitudes toward online dating among students studying in Austria. We are especially interested in researching the usage of da- ting sites as well as gender and user status differences in attitudes toward onli- ne dating among these students. The results, gathered through empirical resear- ch, show that these students do not have positive attitudes toward online dating. Some gender and user status differences were also identified. According to the results, specific profiling for the target group is offered on the basis of their attitu- des to online dating; such information can be very helpful for online dating provi- ders and advertisers.